2021
DOI: 10.3390/su131910810
|View full text |Cite
|
Sign up to set email alerts
|

From Lean 5S to 7S Methodology Implementing Corporate Social Responsibility Concept

Abstract: Introducing methodologies that promote innovation and continuous improvement in organizations is no longer optional; therefore, organizations are increasingly using methodologies based on Lean principles. Among them, the 6S tool stands out from the rest, commonly used to establish and maintain a high-quality environment, which it has capacity for due to its status as a kaizen process. Thus, this research seeks to evaluate the relationship between Corporate Social Responsibility and the Lean 6S tool and, in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 35 publications
(39 reference statements)
0
5
0
Order By: Relevance
“…As a result, this is the first study of its kind in a developing country context, specifically in Palestine, to focus on the manufacturing sector. Finally, past research has revealed no integrated conceptual framework for merging TQM and CSR activities to improve organizational performance (Fernández Carrera et al ., 2021; Khurshid et al ., 2018). This study presents a conceptual framework to understand TQM, CS and CSR linkages.…”
mentioning
confidence: 99%
“…As a result, this is the first study of its kind in a developing country context, specifically in Palestine, to focus on the manufacturing sector. Finally, past research has revealed no integrated conceptual framework for merging TQM and CSR activities to improve organizational performance (Fernández Carrera et al ., 2021; Khurshid et al ., 2018). This study presents a conceptual framework to understand TQM, CS and CSR linkages.…”
mentioning
confidence: 99%
“…It is also worth emphasizing that, as the founders of Lean Management declare, this concept has never been aimed at increasing only the financial results of enterprises. There is a strong social aspect to this concept, as evidenced recently by the inclusion of safety (6S) and environmental (7S) aspects (Fernández Carrera et. al., 2021).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The 5S tool is considered a strategy for business excellence and is also commonly used to establish and maintain a high-quality environment in an organization. [15] 5S is a management model tool that is usually used to work with more efficiency, create a better work environment and continuous production; that is related to minimizing losses, maximizing the final delivery of the product or service [16]. To complement the 5S tool, process standardization is also applied.…”
Section: S Tool Applications and Standardized Workmentioning
confidence: 99%